2015
DOI: 10.1007/s10339-015-0673-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of expectations and visual uncertainty upon detection and identification of a target in the fog

Abstract: Detecting a pedestrian while driving in the fog is one situation where the prior expectation about the target presence is integrated with the noisy visual input. We focus on how these sources of information influence the oculomotor behavior and are integrated within an underlying decision-making process. The participants had to judge whether high-/low-density fog scenes displayed on a computer screen contained a pedestrian or a deer by executing a mouse movement toward the response button (mouse-tracking). A v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Effects of ambiguity persist longer in mouse movements, whereby competition resolution becomes evident in eye movements around 200-300 ms after word offset, while it may continue until 500 ms in hand-movement data (Magnuson, 2005). It has also been suggested that eye tracking is more sensitive to pre-attentive processes before initiation of hand movement (Freeman, 2018;Quétard et al, 2015). For this reason, we expected earlier stages in the process of responding to the task to be more closely reflected in the gaze patterns (fixation duration on images of interest), while later stages and total on-line behaviour may be more evident in the hand movement measures (distance travelled with the mouse/path length, peak velocity).…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of ambiguity persist longer in mouse movements, whereby competition resolution becomes evident in eye movements around 200-300 ms after word offset, while it may continue until 500 ms in hand-movement data (Magnuson, 2005). It has also been suggested that eye tracking is more sensitive to pre-attentive processes before initiation of hand movement (Freeman, 2018;Quétard et al, 2015). For this reason, we expected earlier stages in the process of responding to the task to be more closely reflected in the gaze patterns (fixation duration on images of interest), while later stages and total on-line behaviour may be more evident in the hand movement measures (distance travelled with the mouse/path length, peak velocity).…”
Section: Hypothesesmentioning
confidence: 99%
“…Hand movements have been described as high-fidelity, real-time motor traces of the mind (Freeman, Dale, & Farmer, 2011), while participants' gaze behaviour reflects language-mediated eye movements and can be used as a proxy for language processing, as routinely documented in, for example, the Visual World Paradigm (Allopenna, Magnuson, & Tanenhaus, 1998;Altmann & Kamide, 2007;Huettig, Rommers, & Meyer, 2011). Furthermore, eyemovement paradigms can reveal the on-line integration of different sources of information (e.g., phonological, semantic, and visual information) during spoken language processing (Huettig & Altmann, 2005;Huettig & McQueen, 2007;Huettig, Quinlan, McDonald, & Altmann, 2006;Spivey, 2007), while manual action reveals the real-time dynamics of decision-making and the fine-grained effects of resolving conflict and competition (Barca, Benedetti, & Pezzulo, 2016;Barca & Pezzulo, 2012Flumini, Barca, Borghi, & Pezzulo, 2014;Freeman, 2018;Freeman & Ambady, 2010;Freeman, Stolier, Ingbretsen, & Hehman, 2014;Lepora & Pezzulo, 2015;Quétard et al, 2015;Song & Nakayama, 2009). The main purpose of the current study was to investigate the on-line processing of a selection of figurative expressions (idioms and novel metaphors) on the part of highly verbal participants with autism in comparison to neuro-typical controls using eye tracking in combination with hand-movement data.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the analysis of mouse trajectories can capture cognitive complexity in stimulus processing when participants are required to deliver multiple-choice responses. This procedure has been applied to a large number of fields and has proved useful in highlighting cognitive complexity related to negative sentence verification [ 14 ], racial attitudes [ 15 ], perceptions [ 16 ], prospective memory [ 17 ], and lexical decisions [ 18 ]. Duran et al presented a pioneering investigation on lie detection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extant behavioral research suggests the relevance of top-down processes in the use of concepts (Schyns et al, 1998 ; Vermeulen et al, 2009 ), percepts (Bar, 2004 ; Quétard et al, 2015 , 2016 ), and affects (Scherer, 1997 ; Hess et al, 2007 ; Rudrauf et al, 2008 ; Niedenthal et al, 2009 ). For instance, participants' personality (e.g., Campanella et al, 2012 ) or facial expressions (Niedenthal et al, 2009 ) modulate the detection or recognition of emotional facial expressions (EFE).…”
Section: Introductionmentioning
confidence: 99%